Kyrgyz Republic Economic Update, Spring 2017 : A Resilient Economy… on a Slow Growth Trajectory - World Bank Group (World Bank, Washington, DC, 2017)
The first part of the Economic Update analyzes recent macroeconomic trends and presents an assessment of the country's short- and medium-term outlook. The Special Focus Section discusses the state of the country's energy sector, including issues surrounding its financial viability and fiscal implications, as well as the social implications of reform scenarios.